Constituent Power : law, popular rule, and politics (Edinburgh University Press, 2020)
Recent social and political developments, including the presidential elections in the United States, antidemocratic state policies in Hungary and Poland, and the political climate in the rest of Europe have brought questions relating to the position and composition of 'the people' in constitutional democracies to the forefront.